(Pre)-white dwarf stars as measuring tools for yields of AGB nucleosynthesis. Issue Volume 15:Issue S357(2019) (October 2019) - Löbling, Lisa
Abstract: In the helium-rich intershell region of asymptotic giant branch (AGB) stars, slow neutron-capture nucleosynthesis produces heavy elements beyond iron. If the stars experience a final-flash of the He-burning shell, a pulse-driven convection zone establishes, the stars become hydrogen-deficient and exhibit former intershell material at their surfaces. In their subsequent evolution towards the white-dwarf cooling sequence, but still at constant luminosity, a strong stellar wind prevents diffusion to wipe out the information about AGB yields. We present and interpret the analysis results of hydrogen-rich and -deficient post-AGB stars, discuss difficulties in their analysis and review the implications on the understanding of post-AGB evolution.